In vivo immunomodulating activity of wood extracts from Clausena excavata Burm. f - Manosroi A. (2014)
Immunomodulating effects in Balb/C mice of aqueous extract (CEHW) and the Thai folklore preparation (CEHF) of Clausena excavata Burm. f. were investigated. Haemagglutinating antibody (HA) titers at day 0, 7, 14, 21, 28 and 35 from the serum of animals fed or injected intraperitoneally with the extracts for 5 days were compared and evaluated for humoral mediated immunity (HMI). Footpad swelling test was used to determine delayed type hypersensitivity for cell mediated immunity (CMI). CEHW and CEHF injected intraperitoneally and administered orally exhibited the same maximum antibody production of 1/800. Both extracts given orally reached the maximum antibody titer at day 7, which was 2 weeks faster than by intraperitoneal administration. However, antibody titers from CEHW injected intraperitoneally diminished without retaining whereas the CEHF retained for 1 week. Moreover, CEHW gave CMI response more than the CEHF. This study suggested the potential in vivo immunomodulating activities of extracts from Clausena excavata supporting our previous in vitro studies.